Encryption and Decryption Process of RGB Colour Image Using by Matrix Method - N. Avinash; S. Jaraldpushparaj; T. Sathinathan; G. Britto Antony Xavier (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
In this research work, we propose a new technique for RGB colour image encryption based on permutation matrix. The colour image is encrypted into Red, Green and Blue channels where each channel uses a double permutation key technique for assigning a new colour to every pixel of RGB colour image. Each channel is encrypted with a technique known as double permutation key encoding, which assigns a different color to each pixel of an RGB color image. Additionally, we present a novel approach of partite block encryption. The number of possible encryptions is supplied along with a detailed study of the encryption of a 9-pixel image. Additionally, the Matrix representation effectively conveys the decryption process.